Culture of human sebocytes in vitro - Xia, Longqing (Landes Bioscience, 2009)
Acne and seborrhoea are sebaceous gland-related diseases that are also exclusively human diseases. Therefore, fundamental research on human sebaceous cell function and control requires human models in vitro. The human sebocyte culture model was first introduced in 1989. Cultured human sebocytes have been shown to preserve important sebocytic characteristics, although they undergo an incomplete terminal differentiation in vitro. Over the years, modifications of the technique have improved the culture of human sebocytes in vitro, but the primary cultured sebocytes can still be maintained for no more than six passages in vitro. The immortalized human sebaceous gland cell lines SZ95, SEB-1 and Seb-E6E7 have been developed in recent years, which make it possible to get a large number of sebocytes from the same donor culture. Cultured human sebocytes in vitro has become a useful tool in studying sebaceous gland activity and regulation, and understanding the pathophysiological mechanisms and treatment of acne and other sebaceous gland related diseases.